Yoga and mindfulness for anxiety and depression and the role of mental health professionals: a literature review. Issue 1 (9th January 2017) - Butterfield, Nicole; Schultz, Tim; Rasmussen, Philippa; Proeve, Michael
Abstract : Purpose: The purpose of this paper is to examine the role of yoga in the management of anxiety and depression, development of mindfulness and self-compassion and implications for mental health care delivery and mental health professionals, with a specific focus on nursing practice. Design/methodology/approach: A search of electronic databases Scopus, CINAHL, EMBASE, Medline and Cochrane Library was undertaken. Findings: There is growing research evidence supporting the use of yoga as an adjunct or combination therapy for the management of stress, anxiety and depression. Mindfulness has been indicated as a potential mechanism of change but needs further research. Health care professionals may play an important role in supporting consumers to engage in yoga as part of their mental health care. Research limitations/implications: Yoga research to date has been limited by methodological weaknesses including wide variation of yoga practices, styles and teaching methods; difficulties in double-blinding, suitable placebo-control; lack of randomised controlled trials and small sample sizes. The literature highlights that more high-quality yoga and mental health research is needed. Practical implications: The paper introduces the potential role of yoga for anxiety and depression in the health care system and the role of mental health professionals in implementing and promoting holistic yoga-based therapies. Originality/value: This paper proposes a yoga model for mental health and provides insight into a proposed new direction for future mental health care and the role of nursing practice and other mental health professionals.